Zap1 is required for Candida glabrata response to fluconazole. Issue 1 (18th January 2022) - Gaspar-Cordeiro, A; Afonso, G; Amaral, C; da Silva, S M; Pimentel, C
ABSTRACT: The increasing prevalence of fluconazole-resistant clinical isolates of Candida spp . strongly hinders the widespread use of the drug. To tackle this problem, great efforts have been made to fully understand the fungal response to fluconazole. In this work, we show that the role of Zap1 in Candida glabrata goes beyond regulating yeast adaptation to zinc deficiency. In line with our previous observation that deletion of ZAP1 makes yeast cells more sensitive to fluconazole, we found that the mutant CgΔzap1 accumulates higher levels of the drug, which correlates well with its lower levels of ergosterol. Surprisingly, Zap1 is a negative regulator of the drug efflux transporter gene CDR1 and of its regulator, PDR1. The apparent paradox of drug accumulation in cells where genes encoding transporters relevant for drug extrusion are being overexpressed led us to postulate that their activity could be impaired. In agreement, Zap1-depleted cells present, in addition to decreased ergosterol levels, an altered composition of membrane phospholipids, which together should impact membrane function and impair the detoxification of fluconazole. Overall, our study brings to light Zap1 as an important hub in Candida glabrata response to fluconazole. Abstract : The main regulator of zinc deficiency in yeast plays an additional role in the response to fluconazole, one of the most prescribed antifungals in the world.